2009
DOI: 10.3892/or_00000613
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil and oxaliplatin modify the expression profiles of microRNAs in human colon cancer cells in vitro

Abstract: Abstract. MicroRNAs (miRNAs) have recently taken center stage in the field of human molecular oncology. Most of the chemotherapeutics are able to interfere with nucleic acid metabolism and gene expression. The purpose of this study was to determine how 5-fluorouracil (5-FU) and oxaliplatin (L-OHP) modify the expression profiles of miRNAs in HCT-8 and HCT-116 colon cancer cells and whether the pharmacodynamic mechanisms of the chemotherapeutics could rely in part on their influence on miRNA expression. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Work in our lab shows that miR-191 overexpressing breast cancer cells show increased survival in response to chemotherapeutic drug or hypoxia treatment (Nagpal et al, 2013). Altogether these reports suggest prospects of miR-191 being a target for studying chemotherapeutic interference (Zhou et al, 2010). …”
Section: Mir-191 and Cancer Connectionmentioning
confidence: 98%
See 1 more Smart Citation
“…Work in our lab shows that miR-191 overexpressing breast cancer cells show increased survival in response to chemotherapeutic drug or hypoxia treatment (Nagpal et al, 2013). Altogether these reports suggest prospects of miR-191 being a target for studying chemotherapeutic interference (Zhou et al, 2010). …”
Section: Mir-191 and Cancer Connectionmentioning
confidence: 98%
“…Chaudhry et al (2013) have shown miR-191 induction in response to X-ray treatment in human lymphoblast cells (TK6 cell line). However, miR-191 was shown to be rather downregulated in two colon cancer cell lines HCT116 and HCT-8 when treated with chemotherapeutic drugs (5-Fluorouracil and Oxaliplatin; Zhou et al, 2010). Thus, the effects on miR-191 levels may vary depending on the stress or tissue/cell type.…”
Section: Mir-191 and Cancer Connectionmentioning
confidence: 99%
“…Cisplatin Downregulated Ovarian cancer cell lines [165] Suberoylanilide hydroxamic acid Downregulated Human lung carcinoma cell line [166] 5-Fluorouracil Downregulated Colon cancer cell line [167] Bicalutamide Downregulated Prostate cancer cell line [168] miR-107 5-Fluorouracil Upregulated Breast cancer cells [163] Anthranilamide-pyrazolo [1,5-a] pyrimidine Upregulated Neuroblastoma cell [169] miR-140 5-Fluorouracil Upregulated Breast cancer cells [163] miR-140-5p Suberoylanilide hydroxamic acid Upregulated Human lung carcinoma cell line [166] mir-155…”
Section: Pharmacological Insights Of Celf/noncoding Rna Axismentioning
confidence: 99%